Workplace Spirituality terhadap Organizational Citizenship Behavior (OCB) pada Karyawan dan Tenaga Kesehatan - Azami, Rifa; Wibowo, Ugung Dwi Ario; Mildaeni, Itsna Nurrahma; Satata, Dian Bagus Mitreka (PSIMPHONI, 2024)
The success of an organization depends on its human resources. Human resources play a crucial role in achieving organizational goals. An organization must effectively manage its human resources. The success in achieving the organization's vision, mission, and goals can also be assessed by the positive behaviors of employees. Therefore, organizational citizenship behavior (OCB) can serve as a reference for improving and enhancing the quality of existing human resources. This research aims to determine the effects of workplace spirituality on organizational citizenship behavior (OCB) among employees and healthcare workers at JIH Hospital in Purwokerto. This study employed a quantitative approach. The population consisted of 210 employees and healthcare workers at JIH Hospital in Purwokerto. The sampling technique used simple random sampling, resulting in 136 samples of employees and healthcare workers from JIH Hospital in Purwokerto. The measurement tools used in this study were a modified scale of workplace spirituality and a scale of organizational citizenship behavior (OCB). The data analysis technique involved simple linear regression with the assistance of SPSS version 26.00. This research reveals a coefficient of determination (Rsquare) of 0.064, indicating that workplace spirituality contributes effectively by 6.4% to OCB.  Keywords: Employees and Healthcare Workers; Organizational Citizenship Behavior (OCB); Workplace Spirituality